Obesity: a justifiable ground for dismissal from employment? - Ali Mohamed, Ashgar Ali; Shair Mohamad, Mohd Akram (The Malaysian Current Law Journal Sdn Bhd, 2014)
An employee’s incapacity to carry out his requisite duties under an employment contract has been recognised as a legitimate ground for the employer to terminate the employee’s services, provided that such incapacity materially interferes his proper performance of his contractual duties. The purpose of this article is to address the crucial issue as to whether an employer can justifiably terminate the services of an employee because of the latter’s physical or mental incapacity, particularly if this is the result of the employee’s obesity. The paper attempts to conduct a comparative appraisal of the law in some important jurisdictions namely, European Union, United Kingdom, United States of America, Canada, Philippines, New Zealand and Malaysia, with a view to making strong suggestions to persuade the Malaysian legislature to take immediate and effective legislative and other measure to fill in the serious gaps in the laws relating to the rights and protection of the obese employee, which are glaringly absent in the Malaysian legislation. Accordingly, the paper will propose for the inclusion of a protective provision on the above subject-matter in the Malaysian Persons with Disabilities Act 2008. In fact, there is an on-going intense debate concerning the nature, causes and severe consequences flowing from obesity or excess body weight, not only among health care professionals and policy makers but also particularly in employment law. Academic and empirical studies have shown that obesity can not only seriously impede the obese employee’s ability to carry out his day to day activities, but also restrict his mobility and increase the risks of occupational injuries and illness. Having to deal with an employee’s prolonged absence due to sickness or injuries due to obesity can cause difficult problems to the employer.